Ideal set-up angle between a pair of oval dental magnetic attachments for suppression of the loss in retentive force associated with horizontal displacement. Issue 8 (August 2022) - Takahashi, Masatoshi; Yamaguchi, Hirofumi; Takada, Yukyo
Abstract: Two oval sandwich type magnetic attachments set up in various angulations and spacing, then the pattern of retentive force against horizontal displacement studied. A measuring device and methodology that matches ISO 13017 was used. A pair of magnetic attachments fixed on the same plane at a specific distance on the measuring device and set in various angulations. Retentive force readings of magnetic attachments in various setup positions against the horizontal displacement along the major or minor axis directions were taken. The pattern of decline in retentive force as horizontal displacement increased was different across the various set-ups. It was found that the decrease in retentive forces associated with horizontal displacement can be suppressed when the angle between the major axis and the direction of movement is as small as possible. Formation of a 90° angle between major axes of any pair of magnetic attachments led to nullification of the decline in retentive forces associated with displacement in any direction. Therefore, 90° is the practical, ideal set-up angle between any pair of dental magnetic attachments critical for suppression of the loss in retentive force associated with horizontal gap. Abstract : Dental magnetic attachment, Retentive force, Horizontal gap, Set-up angle.